High‐Rate Accumulation of Tiny Aqueous Droplets Using a Pyroelectrohydrodynamic Jet System. Issue 3 (30th July 2021) - Tkachenko, Volodymyr; Schwödiauer, Reinhard; Rega, Romina; Itri, Simona; Mugnano, Martina; del Giudice, Danila; Ottevaere, Heidi; Nie, Yunfeng; Ferraro, Pietro; Grilli, Simonetta
Abstract : It is well known how the quantification of tiny amounts of molecular species in biological assays is a crucial issue. Herein, a deep investigation on a pyroelectrohydrodynamic jet system is presented in aim to demonstrate its capability to accumulate a large number of tiny aqueous droplets on the surface of a target slide with high efficiency. It makes use of the pyroelectric effect in a lithium niobate crystal for producing a continuous jetting of tiny droplets, thus reducing drastically the volume of sample required for successive biochemical reactions. The performance of the system in terms of electrical field and crystal size is characterized experimentally as well as numerically. An optimal condition is found that produces the deposition of more than 100 pL‐sized droplets in 14 s. Thus, a possible 70‐fold increase in the analyte concentration in the overlap region with a diameter of less than 40 μm is estimated, compared with an individual droplet deposition. Moreover, in case, an additional increase can be achieved simply by extending the droplet accumulation time. This approach may find application in all of those crucial biological assays where highly diluted analytes could be detected by increasing the density of molecules per unit area. Abstract : The pyroelectrohydrodynamic jet system is designed for high‐rate accumulation of picoliter aqueous droplets on a restricted area of a commercial microarray slide. The pyroelectric crystal geometry is optimized in terms of the magnitude and characteristic decay time of the generated electric field. Volume and deposition location statistics are reported for over 100 droplets dispensed during 14 s.